The role of the convection electric field in filling the slot region between the inner and outer radiation belts. Issue 2 (28th February 2017) - Califf, S.; Li, X.; Zhao, H.; Kellerman, A.; Sarris, T. E.; Jaynes, A.; Malaspina, D. M.
Abstract: The Van Allen Probes have reported frequent flux enhancements of 100s keV electrons in the slot region, with lower energy electrons exhibiting more dynamic behavior at lower L shells. Also, in situ electric field measurements from the Combined Release and Radiation Effects Satellite, Time History of Events and Macroscale Interactions during Substorms (THEMIS), and the Van Allen Probes have provided evidence for large‐scale electric fields at low L shells during active times. We study an event on 19 February 2014 where hundreds of keV electron fluxes were enhanced by orders of magnitude in the slot region and electric fields of 1–2 mV/m were observed below L  = 3. Using a 2‐D guiding center particle tracer and a simple large‐scale convection electric field model, we demonstrate that the measured electric fields can account for energization of electrons up to at least 500 keV in the slot region through inward radial transport. Key Points: We connect in situ electric field measurements to slot region flux enhancements for 100s keV electrons An increase in convection can explain enhancements for electrons up to 500 keV near L  = 3 through inward radial transport Our convection model does not match higher‐energy flux observations, indicating a transition point where other mechanisms are required